2021
DOI: 10.1101/2021.12.17.473113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-clinical evaluation of antiviral activity of nitazoxanide against Sars-CoV-2

Abstract: To address the emergence of SARS-CoV-2, multiple clinical trials in humans were rapidly started, including those involving an oral treatment by nitazoxanide, despite no or limited pre-clinical evidence of antiviral efficacy. In this work, we present a complete pre-clinical evaluation of the antiviral activity of nitazoxanide against SARS-CoV-2. First, we confirmed the in vitro efficacy of nitazoxanide and tizoxanide (its active metabolite) against SARS-CoV-2. Then, we demonstrated nitazoxanide activity in a re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…1 ). Nitazoxanide was recently reported to inhibit SARS-CoV-2 infection [9] and we observed similar results ( Fig. S1 ).…”
Section: Resultssupporting
confidence: 91%
“…1 ). Nitazoxanide was recently reported to inhibit SARS-CoV-2 infection [9] and we observed similar results ( Fig. S1 ).…”
Section: Resultssupporting
confidence: 91%
“…In fact, only one preprint posted in December 2021 claimed that both NTZ and TIZ show similar antiviral results in Vero E6 and Caco-2 cells [178].…”
Section: Nitazoxanidementioning
confidence: 99%
“…In February 2020, Wang and colleagues confirmed that NTZ was able to inhibit the novel coronavirus at low micromolar concentrations (IC 50 = 2.12 μM; CC 50 > 35.53 μM), although the antiviral potency of the active metabolite TIZ was absent from the study [ 42 ]. In fact, only one preprint posted in December 2021 claimed that both NTZ and TIZ show similar antiviral results in Vero E6 and Caco-2 cells [ 178 ].…”
Section: Anthelmintic Drugs Against Sars-cov-2mentioning
confidence: 99%